Sarcopenia and frailty as predictor of outcome in critically ill elderly patients with multiple comorbidities - Dina mostafa Elmaleh; Dina Morsy Ahmed Mohamed (The Egyptian Journal of Internal Medicine)
Abstract Background Frailty and sarcopenia are important conditions that grow more common as people age. Frailty, a multi-system illness linked to heightened vulnerability to stresses, and sarcopenia, a loss of muscle mass and function, both raise the likelihood of unfavorable health outcomes including disability or death. This work’s objective was to study the clinical utility of sarcopenia and frailty in critically ill elderly patients with multiple comorbidities. Patients and methods Clinical frailty scale and SARC-F scale questionnaire were done in 70 critically ill patients admitted to geriatric ICU in geriatric hospital. Results There was a highly significant effect of frailty on primary outcomes whether sarcopenia was present or not (which means that effect of frailty on primary outcomes is more prominent than sarcopenia). The associated factors of frailty including primary admission cause, type of associated comorbidities, and primary outcome (mortality, prolonged hospital stay, long-term ICU care) were found to be important. There was a highly significant effect on the presence of sarcopenia regarding mean age, associated comorbidities, and degree of frailty, with a higher percentage for the need of noradrenaline treatment in ICU patients, highly significant relation to patient mortality. Conclusions The risk of death in critical illness is increased by sarcopenia and frailty. Clinical examinations should routinely identify the risk factors for frailty and sarcopenia. By providing appropriate therapies, medical professionals in intensive care units may be able to improve patient outcomes. Clinicians may be able to get prognostic information on the survival and recovery of their frail intensive care unit patients by routinely assessing frailty at the time of admission. Crucially, this might assist patients and their families in making well-informed choices on the course of treatment while they are in critical condition. Crucially, more investigation is needed to ascertain whether there are modifiable elements that might enhance the prognosis of critically sick fragile people.